2019
DOI: 10.1002/qj.3461
|View full text |Cite
|
Sign up to set email alerts
|

Assimilating satellite sea‐surface salinity data from SMOS, Aquarius and SMAP into a global ocean forecasting system

Abstract: Funding informationESA.Measuring Sea-Surface Salinity (SSS) from space is a relatively recent technique that relies on L-band radiometry that has evolved to a point where useful information is provided every few days. The impact of assimilating satellite SSS data is investigated using the global FOAM ocean forecasting system. This system assimilates daily satellite SSS products from the ESA Soil Moisture and Ocean Salinity (SMOS), NASA Aquarius and Soil Moisture Active Passive (SMAP) missions equatorward of 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
(54 reference statements)
1
29
0
Order By: Relevance
“…On the other hand, the results from this paper demonstrate that SSS assimilation improves the near‐surface ocean state leading to improved coupled ENSO forecasts, thus reaffirming and extending our previous results (e.g., Hackert et al, ). Although there are currently very limited data available, the encouraging results of this study and of operational ocean‐only data assimilation experiments (e.g., Martin et al, ; Tranchant et al, ) lead us to expect that assimilation of satellite SSS into more realistic operational forecast systems will result in improved ENSO forecasts. Therefore, we reassert the major conclusions of Tranchant et al () and Martin (), namely, that SSS assimilation should be routinely included as an essential observed quantity for operational coupled modeling since SSS assimilation can offset shortcomings in atmospheric forcing fields of evaporation and precipitation.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…On the other hand, the results from this paper demonstrate that SSS assimilation improves the near‐surface ocean state leading to improved coupled ENSO forecasts, thus reaffirming and extending our previous results (e.g., Hackert et al, ). Although there are currently very limited data available, the encouraging results of this study and of operational ocean‐only data assimilation experiments (e.g., Martin et al, ; Tranchant et al, ) lead us to expect that assimilation of satellite SSS into more realistic operational forecast systems will result in improved ENSO forecasts. Therefore, we reassert the major conclusions of Tranchant et al () and Martin (), namely, that SSS assimilation should be routinely included as an essential observed quantity for operational coupled modeling since SSS assimilation can offset shortcomings in atmospheric forcing fields of evaporation and precipitation.…”
Section: Discussionmentioning
confidence: 72%
“…During a simulation of the 2015 El Niño, Tranchant et al () found that patterns associated with SMOS SSS assimilation acted to enhance the propagation of tropical instability waves in the eastern Pacific and increase the acceleration of the warm/fresh pool migration to the east for the 2015 El Niño. On the other hand, Martin et al () found that the meridional SSS gradient is reduced near 5 °N by SMOS assimilation leading to SL changes and a reduction in tropical instability wave activity and a more zonal North Equatorial Counter Current. Near the equator, SMOS SSS assimilation leads to shallower MLD across the entire Pacific and, the anomalous eastward currents of the 2015 El Niño are enhanced east of 150 °E.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, work to assess the impact of assimilating satellite salinity observations has recently been carried out (Martin et al . ) with a view to future operational implementation. The greatest differences in the upper ocean build over the first 6 months, but it is unclear whether the full effects are realised even by the end of the 13‐month runs.…”
Section: Discussionmentioning
confidence: 99%
“…A common assumption is that errors are Gaussiandistributed and that the time evolution of the errors is linear. As such, there are common limitations to all currently used DA methods and a primary goal for improving the accuracy and applicability of DA in the coming decade will be to relax these limiting constraints (see Martin et al, 2019;Moore et al, 2019, this issue). This has relevance to future ocean-observing system design, as it may change requirements on the observing system either to test and design new methods or to take advantage of new capabilities afforded by the methods.…”
Section: Connecting Ocean Data Assimilation With Ocean Observing Effortsmentioning
confidence: 99%